Dr. Why I am still not Dry: Urodynamic changes after successful VVF repair - Abdullah, Aziz (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the functional outcome of the urinary bladder after successful surgical closure of VVF. Methods: All those patients with VVF who underwent successful surgical repair of VVF (abdominal as well as vaginal) for the 1st time were inducted in the study. Patients with the history of previous VVF repair, previous bladder surgery, bladder trauma and neurogenic bladder were excluded. In total of 96 patients were examined with standard urodynamic studies. Studies were done 4 to 12 weeks after surgical repair. All the surgeries were performed by a single surgeon with a special interest and >15year experience in VVF surgeries. Causes of VVF, time between formation & repair of fistula, bladder capacity, detrusor pressure and any stress or urge incontinence were noted. Results: Mean age of patients were32 [15-72] yrs. 31 cases were of obstructed labor, while remaining were of iatrogenic causes. There was reduction in bladder capacity in all cases but more prevalent in those patients who had vvf for more than 1 year. Around 28% of patient had stress leakage more prevalent in obstructed labor cases. While there was detrusor instability with involuntary contractions in around 50 % of cases increasing with duration of fistula present. Nearly all those leaking had longer duration of fistula and catheterization. Conclusions: Though VVF can be repaired in most of the cases, but consequences remains in forms of reduced capacity and stress and urge incontinence.